1996
DOI: 10.1080/02791072.1996.10472488
|View full text |Cite
|
Sign up to set email alerts
|

Bufo Toads and Bufotenine: Fact and Fiction Surrounding an Alleged Psychedelic

Abstract: This paper investigates the supposedly psychedelic Bufo toad and the allegedly psychedelic drug bufotenine, which is contained in the skin and glands of this toad. The bufo toad has held a place in human mythologies and medicines worldwide since archaic times. Used by ancient peoples for a variety of purposes, its most spectacular effects, according to lore, involve magical and shamanic or occult uses for casting spells and for divination. In the Middle Ages, the Bufo toad was celebrated as a panacea and perse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 219 publications
0
31
0
1
Order By: Relevance
“…Because of its pressor and digitalis-like properties, it was recommended as a heart medication and diuretic and to stop bleeding diathesis [9]. Curiously, German violinists handled toads before performances to reduce' sweat production in their palms [9]; the mechanism through which this is achieved is unclear: no anticholinergic property is described in toad skin secretions. The aphrodisiac properties are likely of central origin, as are other (psychoactive) effects of the drug; hence, it is listed as a hallucinogen.…”
Section: Substances That Increase Libidomentioning
confidence: 98%
See 1 more Smart Citation
“…Because of its pressor and digitalis-like properties, it was recommended as a heart medication and diuretic and to stop bleeding diathesis [9]. Curiously, German violinists handled toads before performances to reduce' sweat production in their palms [9]; the mechanism through which this is achieved is unclear: no anticholinergic property is described in toad skin secretions. The aphrodisiac properties are likely of central origin, as are other (psychoactive) effects of the drug; hence, it is listed as a hallucinogen.…”
Section: Substances That Increase Libidomentioning
confidence: 98%
“…3) and its O-methylated derivative, 5-MeO-DMT (5-methoxy-N,N-dimethyltryptamine), a putative hallucinogen congener of serotonin [9]. It is the active ingredient in West Indian "love stone" and the Chinese medication chan su [10].…”
Section: Substances That Increase Libidomentioning
confidence: 99%
“…The toad venom especially bufotenin secreted by these glands was subject for mythological, pharmacological and medicinal practices for centuries [11]. The Scientific research has confirmed the presence of bufalin in "Chan Su" a traditional Chinese medicine prepared from dried white secretion of the skin glands of Chinese toad used as a drug for treating heart disorders, heamorrhage of gums, sinusitis and other systemic illnesses [12].…”
Section: Introductionmentioning
confidence: 92%
“…Bufotenin (also known as cinobufotenine, mappin, N,N-dimethylserotonin, DM5-HT, 5-OH-DMT), a positional isomer of psilocin, is found in the skin of various species of the toad Bufo genus, in mushrooms such as Amanita, in plants such as Anadenanthera peregrina and Piptoderma peregrina [158]. Its psychoactivity is mainly due to its enzymatic conversion to 5-MeO-DMT [159].…”
Section: Tryptaminesmentioning
confidence: 99%